PROBLEMS IN FIXED ASSETS ACCOUNTS AND WAYS TO ELIMINATE THEM - Boymurodov Ilxomjon Mamadaliyevich,; Nuraliyev Behzod Baxtiyor ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the topic "Issues in the Accounting of Fixed Assets and Ways to Address Them." Fixed assets play a crucial role in the production process, but various problems can arise in their accounting. The article analyzes the classification of fixed assets, accounting deficiencies, and their underlying causes. It also examines proposed methods for resolving these issues, including the use of modern technologies and accounting methods. Ultimately, the article offers practical recommendations aimed at effective management of fixed assets and improvement of financial reporting.